2019
DOI: 10.23887/ijssb.v3i4.21505
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Produk Domestik Regional Bruto, Inflasi, Upah Minimum, dan Jumlah Penduduk Terhadap Pengangguran di Indonesia Periode 2011 – 2017

Abstract: A B S T R A KPenelitian ini merupakan penelitian kuantitatif dengan tujuan untuk mengetahui pengaruh PDRB, inflasi, upah minimum, dan jumlah penduduk terhadap pengangguran. Data yang digunakan berupa data panel 33 Provinsi selama 7 (tujuh) tahun terhitung dari 2011 -2017. Sumber data berasal dari website resmi Badan Pusat Statistik dan Bank Indonesia. Uji hipotesis dianalisis menggunakan program eviews 9.0. Hasil penelitian membuktikan bahwa (1) Produk Domestik Regional Bruto berpengaruh negatif signifikan ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
6
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 3 publications
5
6
0
5
Order By: Relevance
“…However, the total population has no significant effect on open unemployment in Indonesia. The negative relationship is consistent with the findings population variable with a coefficient of 0.477383 and a probability of 0.6251, so it does not affect unemployment (Brahma et al, 2019). This result is in contrast to previous studies by Gideon (2017), which found that population has a positive effect on unemployment; this is indicated by the increase in Nigeria's population in 2014.…”
Section: Resultssupporting
confidence: 87%
“…However, the total population has no significant effect on open unemployment in Indonesia. The negative relationship is consistent with the findings population variable with a coefficient of 0.477383 and a probability of 0.6251, so it does not affect unemployment (Brahma et al, 2019). This result is in contrast to previous studies by Gideon (2017), which found that population has a positive effect on unemployment; this is indicated by the increase in Nigeria's population in 2014.…”
Section: Resultssupporting
confidence: 87%
“…According to this principle, for each 1% uptick in economic growth, there tends to be an associated decline of approximately 0.5% in the unemployment rate. This theoretical framework gains support from empirical research conducted by Sembiring and Sasongko [1], as well as findings by Yasmin et al [12], both of which underscore the significant negative impact of GRDP on unemployment levels in Indonesia during the period spanning from 2011 to 2017. In addition, Shiferaw [13] and Sanchez & Liborio [14] find that there is the inverse relationship dynamically between GDP and unemployment.…”
Section: Literature Reviewmentioning
confidence: 54%
“…Despite the decrease, the open unemployment rate in Indonesia is still above five percent. According to Sembiring & Sasongko [1], a person is said to be unemployed if he has worked for at least one week and received a wage from the job. Meanwhile, if a person does not work because he does not have a job, is looking for a job, or is waiting for a job call, then he is said to be unemployed.…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, penelitian ini juga sejalan dengan penelitian Sembiring & Sasongko (2019) Hal tersebut sependapat dengan teori pengangguran menurut Sukirno (2012) menyatakan bahwa pengangguran ialah seseorang yang tergolong dalam angkatan kerja, sedang aktif mencari pekerjaan pada suatu tingkat upah tertentu tetapi belum mendapatkan pekerjaan yang diinginkannya. Disimpulkan bahwa pekerja menentukan tingkat upah yang diinginkannya untuk suatu pekerjaan yang diinginkannya.…”
Section: Pengaruh Upah Minimum Kota (Umk) Terhadap Pengangguranunclassified